Comparison of the Global Initiative for Asthma Guideline–based Asthma Control Measure and the Childhood Asthma Control Test in Evaluating Asthma Control in Children - Hong-Ren Yu; Chen-Kuang Niu; Ho-Chang Kuo; Ka-Yin Tsui; Chih-Chiang Wu; Chien-Hung Ko; Jiunn-Ming Sheen; Eng-Yen Huang; Kuender D. Yang (Pediatrics and Neonatology)
Reliable assessment of asthma control is essential for effective treatment. While several validated tools for assessing asthma control in children are currently available, few studies have evaluated the correlations between different asthma control measures in children. This study aimed to determine the correlations between the Childhood Asthma Control Test (C-ACT) and the Global Initiative for Asthma (GINA) guideline-based asthma control measure (ACM) with lung function parameters in children with asthma. Methods: Sixty-three children aged 6-11 years with mild-intermittent to severe-persistent asthma were evaluated. They completed the C-ACT, the GINA guideline-based assessment and lung function tests with the help of their caregivers. Results: C-ACT scores and GINA guideline-based ACM were positively correlated. The average C-ACT scores for children with controlled, partly controlled and uncontrolled asthma according to the GINA guidelines were 24.4 ± 0.3, 22.8 ± 0.6 and 21.3 ± 1.0 (mean ± SE), respectively. High C-ACT scores were also noted in children with uncontrolled asthma based on the GINA guidelines. The GINA guideline-based ACM was correlated with spot spirometry parameters (forced vital capacity, forced expiratory volume in 1 second, and maximal mid-expiratory flow). Conversely, the C-ACT score was not correlated with these spirometry parameters. Conclusions: The C-ACT may overestimate asthma control in certain circumstances. For children with poorly controlled asthma or poor symptom perception, more frequent visits and serial pulmonary function tests are recommended.